REACTION OF RICE VARIETIES TO YELLOW STEM BORER, Scirpophaga incertulas (Walker) POPULATIONS - M. SHESHU MADHAV; G. UMA DEVI, R. ATHULYA, T. UMA MAHESWARI, A. P PADMAKUMARI (The Journal of Research, PJTSAU, 2023)
The effect of two rice yellow stem borer (YSB), S. incertulas populations collected from Rangareddy (RGD) and Medak (MDK)on damage in three varieties of rice viz., PB1, W1263 and TN1 were tested during kharif (wet season) of 2019. Infestation was created by releasing the neonate YSB larvae @ two larvae per tiller onto the plants grown in pots under greenhouse conditions at both maximum tillering stage for dead heart damage and booting stage for white ear damage. The dead heart damage by Rangareddy population of yellow stem borer ranged from 19.61 to 35.15 percent, in which PB1 variety showed maximum damage. The yellow stem borer population from Medak caused 27.25 to 35.67 per cent dead hearts with maximum damage to PB1 variety. Infestation by neonate larvae of both the populations resulted in maximum White ear damage in PB1, which was significantly different from TN1 and W1263. However, all the three varieties recorded Damage Score 9 on SES scale for white ear damage. Based on the results of the current study, it can be concluded that there is no significant difference in the infestation level of S. incertulas populations collected from Rangareddy and Medak on PB1, W1263 and TN1.